If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x-6=10x+6
We move all terms to the left:
15x-6-(10x+6)=0
We get rid of parentheses
15x-10x-6-6=0
We add all the numbers together, and all the variables
5x-12=0
We move all terms containing x to the left, all other terms to the right
5x=12
x=12/5
x=2+2/5
| 2(3x+2)+1=29 | | 6u-62=4u | | 3y+54=12y | | 18=3/4(36.4-n | | 63=15w-8w | | 21+2f=23 | | 5.31=p9. | | (2x-8)(2x-4)=0 | | 1/3y+8=4 | | 3.4(-3x-11)=-49.3(3x-16) | | 2x+100=70 | | 6m+1.25=6.9 | | -2x+24=4x+6 | | -20=m/14 | | y=22/11 | | 6-4(x+1)=2(3x+2) | | x+2x+x+2x=12 | | (18-x)60=(x-3)40 | | e-(-3)=-19 | | 1/(110000/(1+(1-23)*0.044225)/3600-(x)=0 | | 5x=180-5-125 | | 9(2y+7)-2(5y-28)+7y=29 | | (9.12)y=4 | | 2x+3x=5x-6x | | 10^x+1=0 | | 24.8=8.2x-16.2 | | 3(3z-1)=15+3 | | (4y-4)3y=52 | | 63x^2-100x+32=0 | | 3y-12=-72 | | 17+w=27 | | 2/42(9x+8)=3/7(2x+8) |